'Alleviating the Sum of Human Suffering': The Origins, Attributes and Appeal of Hospital Sunday, 1859–1914. (June 2022) - Ottewill, Roger
Abstract : In many communities, from the mid-Victorian era until well into the twentieth century, one Sunday every year was dedicated to the work of local hospitals and dispensaries. Originating in Birmingham and designated Hospital Sunday, it enabled congregations to remember their responsibilities towards the sick and it raised much-needed funds for what was essentially voluntary provision, prior to the establishment of the National Health Service. In so doing, they were demonstrating their commitment to philanthropy and (for many) the tenets of the social gospel. Hospital Sunday also symbolized an element of interdenominational cooperation, with most denominations participating, at a time when relations between the established church and the Free Churches on other issues could sometimes be fraught. Moreover, it facilitated the engagement of churches with charitable organizations, such as friendly societies. This article aims to explore the origins of Hospital Sunday, to analyse its key attributes, to assess its appeal and to highlight some of the issues which arose during the Victorian and Edwardian eras.